1997
DOI: 10.1111/j.1365-2052.1997.00131.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of five human chromosome 4 orthologues to bovine chromosomes 6 and 17

Abstract: Five loci that map to human chromosome 4 (HSA4) were selected to expand the bovine comparative linkage map. Loci included b-casein (CSN2), basic fibroblast growth factor (FGF2), immunoglobulin J chain (IGJ), interleukin 2 (IL2) and microsomal triglyceride transfer protein (MTTP). Polymorphisms for each locus were identified by either polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) or single-strand conformational polymorphism (SSCP) analysis. The bovine genes for CSN2, IGJ and MTTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“…Located just distal to the centromere of BTA17, BB718 designates a breakpoint for a conserved segment corresponding to HSA4q25-q31. Mapping studies that previously defined this comparative genomic conservation revealed that the bovine orthologs for interleukin 2 and 15 and uncoupling protein 1 mapped to BTA17 in reverse gene order with respect to the centromere (Fisher et al 1997; Sonstegard unpublished; Sonstegard and Kappes 1999b, respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Located just distal to the centromere of BTA17, BB718 designates a breakpoint for a conserved segment corresponding to HSA4q25-q31. Mapping studies that previously defined this comparative genomic conservation revealed that the bovine orthologs for interleukin 2 and 15 and uncoupling protein 1 mapped to BTA17 in reverse gene order with respect to the centromere (Fisher et al 1997; Sonstegard unpublished; Sonstegard and Kappes 1999b, respectively).…”
Section: Discussionmentioning
confidence: 89%
“…Nine bulls that sire paternal half-sib families collectively known as the Illinois Reference and Resource Families (IRRF; [22]) were screened for a polymorphism in bPOU5F1 by single-strand conformational polymorphism (SSCP) analysis as described [23]. Polymerase chain reaction (PCR) products for SSCP analysis were generated using oligonucleotide primers OCT27 (5Ј-GGAAATTGGGAACACAATGGG-3Ј, coding strand) and OCT28 (5Ј-AACAGCAACCTTCGT-TTCGG-3Ј, noncoding strand), which are both located downstream of the predicted stop codon of bPOU5F1 (see Fig.…”
Section: Genetic Mapping Of Bpou5f1mentioning
confidence: 99%
“…The author found a QTL for live weight maps between markers BM1258 and BoLA DRBP on chromosome 23. (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and the distance (in cM, relative positions) between them. BMS2508, BM3026 and TGLA37 (in bold) are the significant effect markers on daily body weight gain trait (DBWG).…”
Section: Discussionmentioning
confidence: 99%